POLA INTERAKSI GENG “KLITIH” DI YOGYAKARTA - Muhammad Reza Achsanu Dwitama; Siany Indria liestyasari; Sigit Pranawa (SOSIO EDUKASI Jurnal Studi Masyarakat dan Pendidikan, 2021)
Klitih/Nglitih comes from the Javanese language, which means looking for activities in your spare time. Meanwhile, "Klitih/Nglitih" in the context of juvenile delinquency means travelling around using a motorcycle that a group of students has carried out. This study aims to explain the background of the "Klitih" that often occurs in Yogyakarta and the pattern of interaction in the "Klitih" group. This qualitative research uses a case study in the "Klitih" group in Yogyakarta. Based on the research that has been done, it is found that revenge and showing off are the backgrounds for "Klitih", which often occurs in Yogyakarta. The recruitment process from members to former members becomes a pattern of interaction repeatedly appearing in the "Klitih" group.